The Financial Feasibility of Lime Farming (C. aurantifolia) in Landono District South Konawe Regency - Orisa Adi Putra; Surni Surni; Abdi Abdi (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
The lime tree is a plant that significantly contributes to economic growth in Landono District, South Konawe Regency. This research aims to determine the feasibility of farming lime in Landono District, South Konawe Regency. The location determination was carried out purposively (purposively) considering that this area is one of the areas that carry out lime tree cultivation. The research was carried out from February to April 2022. The population in this research was 50 farmers. A simple random sampling using the Slovin formula obtained 33 farmers. The variables in this study were the identity of respondents and the feasibility analysis of farming. Data analysis uses feasibility analysis and sensitivity analysis. The research results obtained by calculating the variables in this research are the independence of the feasibility analysis, the NPV/net value is IDR 14,335,362> 0 (positive) with the applicable bank interest rate of 6%, the NBCR calculation value is 1 .87>1, IRR is 43.44%>6%, and the calculation of Payback Period is a return on investment after 23 months. So from the calculation of the feasibility analysis of the business using four feasibility criteria for lime farming in Landono II Village, Landono Subdistrict, South Konawe Regency is feasible to cultivate. Based on the sensitivity analysis of lime farming in Deisa Landono II, Landono Subdistrict, South Konawe Regency, it meets the feasibility assessment criteria for a 10% increase in input costs, a 10% decrease in output costs and a 10% increase in input costs as well as a 10% decrease in output costs simultaneously while other factors are considered constant.